Helminth Infections in an Indigenous Community of Nepal: The Role of Individual and Household Socio-Economic Factors (Global Journal of Medical Research, 2013)
Background and Objective: In Nepal, gastrointestinal helminthiases are endemic in indigenous people living in low laying areas of the country. However, little is known regarding the role of different socio-economic indicators on helminth infections in these communities. The main aim of this study is to identify the relationship between socio-economic factors and helminth infection in an indigenous community in Nepal. Method: A cross sectional survey was conducted in the Gaindakot Village Development committee, Nepal in July to August 2010. Total of 137 people of 10-60 years of age provided faecal samples for parasitology and answered a questionnaire on indicators of their socio-economic conditions. Result: Overall 54.0% of individuals were positive for helminth infection. The higher (74.3%, 69.6%, 57.8%, 56.9% and 63.6%) infection rate was found in the people worked as a laborer, without sanitation, inadequate water source, living in a mudded house and sharing house with animals respectively. The results were statistically significant (P < 0.05) except water use and house type.
Keywords: Helminth infection; Socio-economic factors; Indigenous population; Nepal